If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x-6=2/3(12x+18)x
We move all terms to the left:
5x-6-(2/3(12x+18)x)=0
Domain of the equation: 3(12x+18)x)!=0We multiply all the terms by the denominator
x∈R
5x*3(12x+18)x)-(2-6*3(12x+18)x)=0
Wy multiply elements
15x^2(1-18x(1=0
| 7x-36+1x+9+5x-1=180 | | 3x+14x+10=180 | | 7y-14=8y-21 | | 3p+6=-3+6p | | 8.92=-0.1d+10.9 | | -2x-4=2(x-1)+3 | | –9c=–8c+9 | | 4x-7(3x+7)=28 | | 7.2/x=1.2 | | 5=q+15/10 | | -7(7x-4)=126 | | 18x-45+5x=26 | | 20y+5=24y-1 | | 175m-75m+53,075=55,550-175m | | x+(90-x)-24=180 | | 20y+5=247-1 | | 8x+3=5x+0 | | z=1/4 | | 10-2x=-12x | | 8x+28=10+10 | | -15x+5=3(5x+2) | | 1.4t=1.6-t | | 12+x=30+3x | | 62+4x=10x-10 | | 2x+7=10x-1 | | 3h+6h-2=43 | | 3.32=-8r | | (x-4)(2x+10(27)=180 | | 5.8=z-3.2 | | -2/4x=-10 | | 3x+6+20x-10=180 | | 6x-3x+4+11=45 |